Pengaruh Model Pembelajaran Conseptual Understanding Prosedures Berbantuan Video Kontekstual terhadap Pemahaman Konsep Matematika Siswa Kelas VIII Di SMP Negeri 4 Kintamani - Yana, Yos Sutirta (Jurnal Pendidikan Matematika Undiksha, 2025)
Concept understanding is a crucial element in mathematics learning. Therefore, the aim of this study is to describe the effect of the Conceptual Understanding Procedures (CUPs) learning model assisted by contextual videos on the mathematical concept understanding of eighth-grade students at SMP Negeri 4 Kintamani compared to students taught using conventional learning methods. The population in this study consisted of 137 eighth-grade students at SMP Negeri 4 Kintamani. Two out of four eighth-grade classes were selected, and further random selection determined class VIII-B, consisting of 34 students, as the experimental class, and class VIII-D, consisting of 35 students, as the control class. This study used a quasi-experimental method with a Posttest-Only Control Design, involving 69 students as the sample. The sample was determined using the cluster random sampling technique. The results of this study are indicated by an R-square coefficient of 0.85. The influence of variable X on variable Y is reflected in the t-test value (t_hitung) of 7.805, which is greater than the t-table value (t_tabel) of 3.996. This confirms a relationship between the use of the CUPs learning model assisted by contextual videos and students' understanding of mathematical concepts. Furthermore, the study shows that the average conceptual understanding ability of students using the Conceptual Understanding Procedures (CUPs) learning model is higher than that of students using conventional learning methods.